Pengaruh Tingkat Pendidikan, Masa Kerja, dan Usia Terhadap Etos Kerja Pekerja Harian Lepas Penebasan Pada Bidang Pertamanan Dinas Kebersihan dan Pertamanan Kota Pontianak - Helman Fachri; Zainuddin 01 (JURNAL MANAJEMEN MOTIVASI, 2014)
This study analyzes the influence of education level, Tenure, and the age of the Daily Worker Work Ethics in the Field Landscape Remove slashing the Department of Hygiene and Pontianak. The population in this study are all non-permanent employees slashing at the Parks Division in Pontianak City DKP totaling 67 people. In this study using saturated sampling analytical  method used is the analysis of variance (ANOVA). Based on the results of ANOVA analysis showed that education level had no effect on Work Ethics obtained from the Fhitung 0.220 <3.14 Ftabel meaning H0 is accepted and Ha refused, so results of hypothesis testing showed no difference in education level elementary schools, junior high schools, and High School to Work Ethics, ANOVA analysis results indicate that the Work Period Work Ethics does not affect the results obtained from Fhitung 0.031 <3.14, which means H0 Ftabel accepted and Harefused, so results of hypothesis testing showed no difference Working Period New, Medium and Long to Work Ethics as well as the results of ANOVA analysis showed that age does not affect the Work Ethic obtained from the Fhitung 0.235 <3.14 Ftabel meaning H0 is accepted and Ha refused, so results of hypothesis testing showed no difference Work ethic among young, middle age and old.